Predicting Biology Identity from Plant Literacy, Systems Thinking, and Reflective Judgment: A PLS-SEM Approach - Ismail Ismail; Yusminah Hala; Nurhayati B; Suhartini Azis; Asham Bin Jamaluddin (International Journal of Educational Practice and Policy, 2026)
This study examined the relationships among plant literacy, systems thinking, reflective judgment, and biology identity among university students. Using a quantitative non-experimental approach with a cross-sectional survey design, data were collected in January 2026 from students of the Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar. The data were obtained through a structured questionnaire using a 1–7 Likert scale and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that the measurement model met the required reliability and validity criteria, with all indicator loadings above 0.70, AVE values above 0.50, and HTMT values below 0.90. In the structural model, plant literacy had a positive and significant effect on biology identity (β = 0.603, p < 0.001), and reflective judgment also had a positive and significant effect (β = 0.275, p < 0.001). In contrast, systems thinking had a negative but non-significant effect (β = -0.026, p = 0.647). The model explained 68.6% of the variance in biology identity. These findings indicate that biology identity is more strongly associated with students’ connection to core biological content and reflective engagement with knowledge than with systems thinking as a direct predictor.